Phytochemical screening and analgesic profile of the lyophilized aqueous extract obtained from Chrysobalanus icaco leaves in experimental protocols. (1st December 2016) - Araújo-Filho, Heitor G.; Dias, Jessica Deise Santos; Quintans-Júnior, Lucindo J.; Santos, Márcio R. V.; White, Pollyanna A. S.; Barreto, Rosana S. S.; Barreto, André S.; Estevam, Charles S.; Araujo, Silvan S.; Almeida, Jackson R. G. S.; Menezes, Irwin R. A.; Coutinho, Henrique D. M.; et al.
Abstract: Context: Chrysobalanus icaco L. (Chrysobalanaceae) has been used for the treatment of abdominal pain and cramps. Objective: Assess the chemical and pharmacological profile of the lyophilized aqueous extract from C. icaco leaves (AEC). Materials and methods: Chromatographic methods were used to assess compounds from AEC. Mice were treated with vehicle (control group) or AEC (100, 200 or 400 mg/kg, p.o.) (group with 7–8 mice) and the analgesic profile was assessed employing the acetic acid-induced writhing, formalin, hot plate tests and hyperalgesia induced by carrageenan (CG) or tumour necrosis factor-alpha. The animal motor performance was assessed using rota-rod and grip strength tests. Results: The chromatographic profile of AEC demonstrated the presence of terpenoid compounds. The acute pretreatment with AEC, at all doses, produced a significant ( p < 0.01) inhibition of painful bahaviour (11.4 ± 3.6; 10.3 ± 2.8; 11.3 ± 2.2) when compared to the control group (24.7 ± 4.7) in acetic acid-induced writhing test. In the formalin test, AEC were effective in the second phase ( p < 0.01) (57.2 ± 10.3; 56.3 ± 9.2; 54.7 ± 8.9) when compared to control group (121.9 ± 18.5). No response was observed in the hot plate test. The higher dose of AEC produced a significant ( p < 0.01 or p < 0.05) inhibitory effect on the mechanical hyperalgesia test. AEC did not affect the motor performance of the mice. Discussion: The terpenoids from AEC are known for its analgesic and anti-inflammatory properties. So, these results corroborate the experiments using the AEC in inflammatory pain protocols. Conclusion: Our results suggest that AEC act against inflammatory pain.